Retinopathy of prematurity in preterm infants born following assisted conception versus spontaneously conceived pregnancies – A 2-year retrospective observational study from an urban tertiary eye care referral center in South India - Supriya Dabir; Arthi Mohankumar; D V Srivatsa; Sivakumar Munusamy; T T JM Berendschot; Mohan Rajan; Rajvardhan Azad (Indian Journal of Ophthalmology, 2023)
Purpose: The aim of this study is to determine if in vitro fertilization (IVF) is associated with an increase in the incidence of retinopathy of prematurity (ROP) among preterm infants. Methods: This retrospective, comparative study included all the preterm babies who were screened under an urban multicentric outreach project between April 2019 and August 2022. Infant details including gender, birth weight, mode of conception, single or multiple gestation, gestational age and post-menstrual age in weeks, age at presentation, and any presence of risk factors were recorded and analyzed. Results: Among 444 preterm babies included in the study, 373 (84%) were conceived normally and 71 (16%) were conceived by IVF. ROP was found in 99 (22.29%) babies in total. There was no significant difference in the incidence of any stage of ROP between the two groups; however, higher stages of ROP were found to be relatively more frequent in the spontaneous conception group in our study. We also found a statistically significant difference in the presence of ROP among singletons, twins, and triplets. Conclusion: IVF was found not to independently increase the risk of ROP in preterm infants. More prospective studies and randomized controlled trials are needed to establish the relationship between the mode of conception and development of severe ROP in preterm infants.